Beginning DotNetNuke 4.0 Website Creation in VB 2005 with Visual Web Developer 2005 Express - Symmonds, Nick (Apress, 2012)
Here you are, at the start of this book. You are wondering why you should buy this book as opposed to the many others on the shelf. You may have noticed that this book is not as thick as the others. Does that mean it does not contain as much information? Well, as a matter of fact, yes. This book is about results. It is about getting from point A to point B with as little hassle as possible. I have not filled this book with ancient history and have not included any indepth discussions concerning the technology behind .NET and DotNetNuke. What I have included are the basics to get you going. You will see concise overviews of .NET and DotNetNuke. You will see how using the latest software developments from Microsoft and the open source community can combine to give you a professional web presence. In short, this book has everything you need and nothing you don’t. If you are curious, however, I do point you to other information sources to get more in-depth explanations and examples.